Posterior urethral valves: The value of high diversion - MacKinnon A (Wolters Kluwer Medknow Publications, 2005)
The management of posterior urethral valves remains a challenge to the paediatric urologist. Many cases diagnosed early may be managed by endoscopic surgery. However, where there is a gross upper tract dilatation, consideration needs to be given to temporary diversion to allow recovery of renal function and the elimination of infection. Western literature leans strongly towards nondiversion. However, in those countries, most patients present early, and often by antenatal diagnosis. Countries not having universally, highly developed medical services encounter more of the complicated cases. Evaluation of the role of upper tract diversion in such circumstances has not been conclusively established, but literature review indicates a role in selected cases.